GEGAR BUDAYA PERSPEKTIF KOMUNIKASI ANTARBUDAYA - nanda elma fitriani (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2023)
Culture Shock of Intercultural Communication Perspective. This research focuses on culture shock from the point of view of intercultural communication among employees in the work environment. Because culture shock is a problem that is often encountered by everyone when present in a new environment and culture, especially employees who work at Madiun Umbul Square. So the purpose of this study is to find out how culture shock in the world of work then creates intercultural communication by employees who have pressure in carrying out their work. The method used is descriptive qualitative, using observation, interviews and participation of employees who have an impact on cultural shock in the work environment. Furthermore, the data that has been collected was analyzed using Spradley analysis. The results of the study show that the culture shock experienced by Madiun Umbul Square employees has habits that have the potential to cause negative connotations with different perspectives in communicating. However, in the context of intercultural communication activities in the work environment, Madiun Umbul Square employeescultural is a person who has collectivism. So that it will minimize the birth of negative stereotypes in culture shock.